Plans de sauvegarde et monuments nationaux : réflexion sur les priorités de conservation à propos des collections de moulages - Geneviève Rager (In Situ)
The collections of plaster casts of the architectural decor of nine monuments belonging to the Centre des monuments nationaux were studied in 2013 and 2014. The aim was to envisage their preservation and interpretation. The conditions in which they were stored was preoccupying and there was no question of diffusing the casts. The information obtained allowed for the preparation of a programme of conservation and restoration and the improvement of the conditions in which the casts are kept. Solutions were envisaged and budgeted in order to create local reserve collections. The article addresses the problem of how to prioritise urgencies.